No guarantees : the experiences of women in casual work : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in Social Policy at Massey University - Dowdeswell, Sarah (Massey University, 1998)
Over the last few decades there has been a growing number of casual workers in New Zealand. Many of these workers are not adequately counted in statistics and little is known about the nature of their work or the impact this has on their lives. It is assumed that the majority of these casual workers are women (Davidson and Bray, 1994, Else, 1996, Shirley, 1996) This thesis examines the experiences of women in casual work. The primary source of data for this thesis is twelve indepth interviews with women involved in casual work. The women were encouraged to tell their own stories and relate their experiences. The thesis examines why these women are in casual work and examines what, if any, choice was available to the women. The research investigates the working conditions of the women's casual work. It then looks at the impact that casual work has on the women's personal lives. The women relate experiences which show how casual work has affected their finances, their health and their families. The thesis highlights how the different circumstances of each woman governs the extent to which casual work affects them. The results showed that while casual work was a positive experience for some women, it was a negative experience for others who were more vulnerable to the insecurity casual work can bring. Generally those women who were not reliant on the income from their casual work to provide for the needs of themselves and their family had more power to negotiate better conditions of work than women who relied on the casual work to provide a basic household income. The degree of need was also a predicator of the negative impact casual work had on the personal life of some women.
Keywords: Casual labor; Women; New Zealand; Employment